1994
DOI: 10.1023/a:1018931820564
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The modification of surface properties of biodegradable poly(lactide-co- glycolide) (PLGA) and model polystyrene nanospheres by poly(lactide)-poly(ethylene glycol) (PLA:PEG) copolymers has been assessed using a range of in vitro characterization methods followed by in vivo studies of the nanospheres biodistribution after intravenous injection into rats. Coating polymers with PLA:PEG ratio of 2:5 and 3:4 (PEG chains of 5000 and 2000 Da. respectively) were studied. The results reveal the formation of a PLA:PEG c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(60 citation statements)
references
References 10 publications
2
57
1
Order By: Relevance
“…A general reduction in zeta potential was observed when the nanospheres were coated with the block co-polymers. This is attributed to the masking of the inherent negative charge of the nanospheres (carboxyl groups in the polymer end groups [10]). The PEO chains bring about a shift in the shear plane to a distance further from the nanosphere surface [11].…”
Section: Resultsmentioning
confidence: 99%
“…A general reduction in zeta potential was observed when the nanospheres were coated with the block co-polymers. This is attributed to the masking of the inherent negative charge of the nanospheres (carboxyl groups in the polymer end groups [10]). The PEO chains bring about a shift in the shear plane to a distance further from the nanosphere surface [11].…”
Section: Resultsmentioning
confidence: 99%
“…The same observations have been reported for PLGA-PLA : PEG coated nanoparticles. 28) Our experimental results showed that PEG-PHDCA nanoparticles could extend the half-life of rHuTNF-a to 7.42 h and obviously change the protein biodistribution in tissues, in particular, increase accumulation of rHuTNF-a in tumor. This result confirmed the idea of forming nanoparticles with a steric PEG barrier that would prevent their rapid uptake by MPS, improve circulatory half-life of rHuTNF-a and also contribute to the enhanced vascular permeability of tumors compared with normal tissues.…”
Section: Discussionmentioning
confidence: 68%
“…In medicine, the polymer has been incorporated in several drugs such as oral sustainedrelease tablets [1][2][3][4][5] and ocular inserts. 6 in addition, it has been shown that particles with poly(ethylene oxide) surfaces have great potential as long circulating systems after intravenous administration [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%